The Psychometric Properties of the Norwegian version of Autism Diagnostic Interview- Revised (ADI-R) - Halvorsen, Marianne; Helverschou, Sissel Berge (PsykTestBarn, 2017)
Description: ADI-R is a semi-structured interview developed by Sir Michael Rutter, Ann Le Couter and Cathrine Lord to provide valid and reliable diagnostics of Autism Spectrum Disorders. The first version was published in 1989 by Western Psychological Services and a revised version in 1994 (ADI-R). The Norwegian version was developed by Hogrefe in 2009. There is a Norwegian protocol and an American manual available for users. The interview can be used to assess both adults and children above the age of 12 months and with mental age above 10 months. ADI-R consists of 93 items. The interview lasts 1.5–2.5 hours. To administer the ADI-R, an experienced clinical interviewer questions a parent or caretaker who is familiar with the developmental history and current behaviour of the individual being evaluated. Cut-off values are calculated by a diagnostic algorithm to give an indication of suspicion of an autism spectrum disorder. Literature search. Literature search: A systematic search for psychometric evidence for the Norwegian, Swedish and Danish versions of the ADI-R identified 190 articles. Experts suggested three additional articles. The included publications reported data from one population-based Norwegian study of totally 679 participants, in addition to six clinical studies from Sweden, in which the largest study included 268 participants. The majority of the participants were children and adolescents. Psychometrics. Psychometrics: The diagnostic validity of the new toddler algorithms of the ADI-R gave lower sensitivities compared to the original American validation studies. The convergence of the ADI-R and Autism Diagnostic Observation Schedule-2 (ADOS) showed mixed results. The inter-rater reliability for single ADI-R algorithm items, behavioral domains totals and agreement for diagnostic classification is good. Characteristics such as child age, IQ and conduct problems, in addition to parental concern for ASD, can influence the construct validity of the ADI-R. Conclusion. Conclusion: There are no Norwegian or Scandinavian norms available. The diagnostic validity of the new toddler algorithms is acceptable when combined with direct observation through the ADOS. Child and caregiver characteristics may hamper the construct validity of the ADI-R. Further studies should investigate the construct validity of the ordinary diagnostic algorithms in addition to instrument reliability.